EFFICIENCY EVALUATION OF IN-HOUSE SOFTWARE FOR CONTROL COMPUTING FACILITIES OF DATA TRANSMISSION SYSTEMS - Khudoyberdiev Rahmatillo (American Journal of Applied Science and Technology, 2024)
The article discusses the justification and selection of criteria for evaluating the effectiveness of software used in control computing facilities (CCF) for data transmission systems (DTS). It focuses on two main types of CCS with a multi-step program execution pattern and a limited number of load sources. The effectiveness of in-house software by using statistical modeling of CCF functioning is also evaluated in the article. It proposes a methodology for assessing the in-house software's effectiveness for CCF of DTS, which would help determine how well the developed software meets the basic requirements for CCF functioning.